The hidden risk factors behind of suicidal behavior in medical students: a cross-sectional cohort study in Mexico - Martinez-Fierro, Margarita L.; Reyes-Hurtado, Jorge R.; Ayala-Haro, Anayantzin E.; Avila-Carrasco, Lorena; Ramirez-Hernandez, Leticia A.; Lozano-Razo, Georgina; Zavala-Rayas, Javier; Vazquez-Reyes, Sodel; Mauricio-Gonzalez, Alejandro; Velasco-Elizondo, Perla; Juarez-Alcala, Vladimir; Flores-Vazquez, Ricardo; et al. (Frontiers in Psychiatry, 2025)
IntroductionSuicidal behavior among medical students is a significant concern, requiring a thorough understanding of effective intervention and prevention strategies. This study aimed to generate a situational diagnosis and establish the risk factors associated with suicidal behavior among medical students.MethodsIn a cross-sectional cohort design, we surveyed 688 medical students in Zacatecas, Mexico, employing 14 validated questionnaires to assess suicidal behavior, aspects of their lifestyle, perceived support, risk factors including mental health disorders, and substance use. Univariate and multivariate analyses were performed to examine the associations between the study variables and suicidal behavior.ResultsSuicidal behavior was associated with the following variables: female sex, non-heterosexual orientation, history of psychiatric illness, childhood trauma, bullying, symptoms suggestive of attention-deficit/hyperactivity disorder (ADHD), and contexts of substance use such as unpleasant emotions (p <0.05). Multivariate analysis revealed that mild tobacco use, alcohol consumption, severe hopelessness, family history of mental disease, material, and affective support significantly increased the odds of suicidal behavior (OR values: 1.56–8.78, p <0.05). Anhedonia, sexual orientation, and problematic consumption of cannabis were significantly associated with suicide attempts, with higher OR of 9.92, 6.49, and 5.56, respectively.ConclusionsSexual orientation, substance use, lack of material, and affective support were identified as significant risk factors for suicidal behavior and suicide attempts among medical students. Additionally, hopelessness, history of mental health diseases, and ADHD symptoms were associated with an increased risk. These findings underscore the need for targeted interventions that include behavior modification for substance use and the reinforcement of emotional and social support networks.